2014
DOI: 10.1149/2.0171411jes
|View full text |Cite
|
Sign up to set email alerts
|

A Phase-Field Model Coupled with Large Elasto-Plastic Deformation: Application to Lithiated Silicon Electrodes

Abstract: A phase-field model, accounting for large elasto-plastic deformation, is developed to study the evolution of phase, morphology and stress in crystalline silicon (Si) electrodes upon lithium (Li) insertion. The Li concentration profiles and deformation geometries are co-evolved by solving a set of coupled phase-field and mechanics equations using the finite element method. The present phase-field model is validated in comparison with a non-linear concentration-dependent diffusion model of lithiation in Si elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 46 publications
7
105
0
Order By: Relevance
“…In these regards, a phase field model may be advantageous over the discrete tracking method in finite element framework since phase field models naturally track the phase boundary with a controllable width. A recent phase field model 54 for simulating lithiation of c-Si demonstrated that the phase field model provides nearly equivalent results as the fronttracking finite element method.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these regards, a phase field model may be advantageous over the discrete tracking method in finite element framework since phase field models naturally track the phase boundary with a controllable width. A recent phase field model 54 for simulating lithiation of c-Si demonstrated that the phase field model provides nearly equivalent results as the fronttracking finite element method.…”
Section: Governing Equationsmentioning
confidence: 99%
“…In parallel to these experiments, models of different length scales have been established, ranging from first-principles simulations, [25][26][27][28][29][30][31][32][33][34][35][36] molecular dynamics with empirical force fields on the atomic scale, [37][38][39][40][41][42] continuum-level simulations that couple field equations dictating Li transport and mechanical equilibrium. 9,12,[43][44][45][46][47][48][49][50][51][52][53][54][55] Together, this has opened a bottom-up avenue for developing high-performance LIBs, in contrast to the top-down approach adopted by the conventional battery development.…”
Section: Introductionmentioning
confidence: 99%
“…The concurrent processes of Li transport, phase transformation and elasto-plastic deformation in Si anodes have inspired numerous modeling works [19][20][21][22][23][24][25] . Several groups developed models to explain the anisometric volume expansion of c-Si nanowires upon lithiation 14,18,24 .…”
Section: Introductionmentioning
confidence: 99%
“…31,33 The Cahn-Hilliard formulation based two phase transport model has been utilized by Chen et al to model combined lithium diffusion and motion of the two-phase interface. 34 A similar formulation is adopted to capture two-phase diffusion in silicon in the current study.…”
mentioning
confidence: 99%
“…39 Large elastic-plastic deformation of silicon has been incorporated in a few computational studies. 29,34 Lattice spring model based high volume expansion modeling has been shown to replicate the deformation of silicon and tin electrodes. 40,41 However, there are no detailed numerical analyses investigating the effect of the diffusion mechanism on fracture tendencies inside silicon particle with surface film mimicking solid electrolyte interphase or secondary phase layer.…”
mentioning
confidence: 99%